Response of grassland ecosystem function to plant functional traits under different vegetation restoration models in areas of karst desertification - Song, Shuzhen; Xiong, Kangning; Chi, Yongkuan (Frontiers in Plant Science, 2023)
Plant functional traits serve as a bridge between plants, the environment, and ecosystem function, playing an important role in predicting the changes in ecosystem function during ecological restoration. However, the response of grassland ecosystem function to plant functional traits in the context of ecological restoration in the karst desertification areas remains unclear. Therefore, we selected 5 plant functional traits of plant height (H), specific leaf area (SLA), leaf dry matter content (LDMC), root length (RL), and root dry matter content (RDMC), used community-weighted mean (CWM) and functional trait diversity, and combined with 10 indexes related to ecosystem function to investigate the differences in plant functional traits and ecosystem functions as well as the relationship between plant functional traits and ecosystem functions in four ecological restoration modes (Dactylis glomerata (DG), Lolium perenne (LP), Lolium perenne + Trifolium repens (LT) and natural grassland (NG) ) in this study. We found that: 1) The Margalef index and Shannon-Wiener index of plant species in DG and LP were significantly lower than those in NG (P <0.05), while the Simpson index was significantly higher than that in NG (P <0.05). 2) The CWMH, CWMLDMC and CWMRDMC in DG, LP and LT were significantly higher than those in NG, but the CWMSLA was significantly lower than that in NG (P<0.05). The functional richness index (FRic) in DG and LP was significantly higher than that in NG and LT, but the functional dispersion index (FDis) and Rao's quadratic entropy index (RaoQ) were significantly lower than that in NG and LT (P<0.05), and there was no significant difference between DG and LP, NG, and LT (P>0.05). 3) The ecosystem function, including ecosystem productivity, carbon storage, water conservation and soil conservation, was highest in LT and lowest in NG. 4) CWMLDMC (F=56.7, P=0.024), CWMRL (F=28.7, P=0.024), and CWMH (F=4.5, P=0.048) were the main factors affecting ecosystem function. The results showed that the mixed pasture of perennial ryegrass and white clover was more conductive to restoring ecosystem function. This discovery has important implications for the establishment of vegetation, optimal utilization of resources, and the sustainable development of degraded karst ecosystems.